Industrial Applications of Hemp Fiber in Europe and Evolving Regulatory Landscape - Jerónimo González Cortés; Byeong Ryeol Ryu; Christopher Pauli; Luis Royano Barroso; Sang-Hyuck Park (Journal of Natural Fibers)
In Europe, hemp fiber has historically been utilized in textile, paper, and construction industries prior to the emergence of synthetic fibers. The demand for hemp fibers in the European Union (EU) has led to a significant increase in cultivation area, rising by 46.5% from 22,010 hectares (ha) in 2016 to 32,250 ha in 2022. Recently, the European Parliament relaxed hemp regulations by raising the allowable THC level from 0.2% to 0.3%. France stands as the largest hemp fiber producer, contributing 78% of EU production, equivalent to 121,720 tonnes in 2022. This increase in production is driven by the fibers’ use in textiles, clothing, paper, and hemp seed in food products. Notably, the building industry has seen a rise in the use of hemp, particularly in materials such as hemp insulation and hemp concrete. Furthermore, innovations in hemp include the development of bioplastics and the replacement of glass fibers with hemp fibers in the automotive sector. This review explores the regulatory landscape, industrial applications of hemp fiber, and the future potential of hemp by-products as alternative agricultural commodities in EU countries.